Pengembangan Aplikasi Analisis Sentimen Terhadap Rencana Pemindahan Ibu Kota Negara Republik Indonesia - Rudy Yohanes Liemawan (UNIVERSITAS KALBIS, 2023)
This study aims to classify the sentiments of public opinion on the plan to move the country's capital city from Jakarta to Nusantara. The data is from Twitter, with 570 tweets taken on March 21-30, 2022. The software development method used is the incremental method. The tweets are divided into two parts. The first part has 285 tweets for the first increment and the rest for the second increment. The first part has 242 positive tweets and 43 negative ones. This study uses the Bernoulli Naïve Bayes method. The evaluation results of the sentiment analysis model obtained an average accuracy of 82.46%, precision of 95.02%, recall of 85.79%, and f1-score of 90.12%. Then the application results in the second incremental stage can be used to predict sentiment from 285 tweets that have not been labelled.